2016
DOI: 10.1016/j.cep.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of centrifugal serpentine micromixers and analyzing mixing quality parameters

Abstract: Centrifugal microfluidics or the Lab on a CD (LOCD) has developed vast applications in biomedical researches and analyses. Fluid mixing is an application of the LOCD. In this paper, multiple centrifugal micromixers were simulated. Various parameters were originally presumed to have an effect on mixing performance. These parameters include inlet angle, angular velocity, cross-sectional profile, perpendicular length ratio and the number of channels in series. They were each analyzed through simulations. It was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Furthermore, remarkable mixing quality has been achieved for the biological fluids using the proposed model which would make it appropriate for all biological applications. Of particular interest is the experimental implementation of the studied micro mixer, details of which will be addressed in our future studies based on this study and our previous numerical simulations [25][26][27]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, remarkable mixing quality has been achieved for the biological fluids using the proposed model which would make it appropriate for all biological applications. Of particular interest is the experimental implementation of the studied micro mixer, details of which will be addressed in our future studies based on this study and our previous numerical simulations [25][26][27]. …”
Section: Resultsmentioning
confidence: 99%
“…Centrifugal forces can also enhance mixing and has been used in lots of micromixers [ 87 , 88 , 89 ]. Haeberle et al [ 90 ] reported a centrifugal micromixer, relying on the Coriolis force induced by the rotated plate to drive and mix the fluids ( Figure 10 a).…”
Section: Active Micromixersmentioning
confidence: 99%
“…Aside from a proven ability to reach the necessary mixing quality, passive designs benefit from being accessible to a variety of fabrication methods including soft lithography [39,40], 3D printing [41], and molecular imprinting [42]. This, together with accurate computational modeling of the fluid and reactant dynamics in these devices accessible through a variety of popular CFD packages, has enabled an efficient pipeline for the design, optimization, prototyping, and testing of passive mixers [33,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%